Root Growth Responses of Melilotis indicus (L.) All. to Air Pollution - Saquib, Mohammad (Ecoprint: An International Journal of Ecology, 2010)
The root length, root biomass and net primary productivity of Melilotus indicus were studied at the monthly intervals from a wheat cropland, growing at the four selected sites situated at 0.5, 2, 4 and 20 km leeward from the source of pollution caused by coal burning of a thermal power plant of Kasimpur (U.P, India). Root growth varied with the level of pollution, age of the stand and the coal consumption rate as well as the release of major gases from the power plant. The data indicate that the degree of response increased with decreasing distance from the source of pollution. The root length and root biomass were affected significantly at the 0.5 and 2 km. respectively in the seedling stage, while in the middle and old stages the loss significantly increased up to 4 km in comparison to the reference site situated at 20 km away from the source of pollution. The percent loss in the root growth of M. indicus increased from seedling to middle stage and decline at the old stage. Root length, root biomass and net primary productivity suffered greater in the middle stage, may be due to high coal consumption and greater release of gaseous pollutants from the power plant. The root length and root biomass showed a significant positive relationship with the distance from the source. Key words: Air pollution, root growth, Melilotus indicus, wheat cropland, biomass. DOI: 10.3126/eco.v16i0.3470 ECOPRINT 16: 29-34, 2009